Optimizing Islamic Education Management in Improving the Quality of Learning in Schools - Efendi, Daud Rahmat (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The low quality of learning in schools, which is influenced by the less than optimal management of Islamic education. This study aims to identify and analyze strategies for optimizing Islamic education management to improve the quality of learning in the school environment. This study uses a library research method, namely by collecting, reading, and analyzing various relevant literature, such as books, journals, documents, and previous research results related to education management and the quality of Islamic education learning. Data were analyzed qualitatively with a descriptive approach, emphasizing the understanding of concepts, principles, and implementation of Islamic religious education management from various library sources. The results of the study indicate that optimization of Islamic education management can be carried out through several strategic steps, including: strengthening the role of school principals and Islamic education teachers in planning and evaluating learning, developing adaptive and contextual curricula, increasing the competence of educators through ongoing training, and utilizing information technology in the learning process. With the implementation of optimal management, the quality of Islamic education learning in schools can increase significantly, reflected in the increase in understanding, attitudes, and religious behavior of students. The research contribution is expected to be a reference for policy makers, practitioners, and academics in developing holistic and effective Islamic Education management to produce a generation that excels intellectually, emotionally, and spiritually.